Phytochemical Screening and In Vitro Antioxidant Activity of Three Nepalese Plants - Poudel, Samiksha; Adhikari, Sabina; Tiwari, Anil; Acharya, Shiva; Chhetri, Sumit Bahadur Baruwal; Adhikari, Rupesh; Poudel, Prakash; Khatri, Deepa (Journal of Nepal Chemical Society, 2024)
Nepal is rich in plant resources and holds the 49th spot in the world’s biodiversity. The variation in altitude, climatic conditions, and geographical features across Nepal make it a rich source of Medicinal and Aromatic Plants (MAPs). The study was carried out to perform the preliminary phytochemical screening and assess antioxidant properties in Ficus neriifolia, Rubus treutleri, and Periploca calophylla. Plants were selected based on their ethnomedical use and scant scientific research. Ethanol (70%) and aqueous extracts were prepared by using the cold maceration method and preliminary phytochemical screening was conducted using the previously established method to test the presence of biologically active phytoconstituent. In vitro, antioxidant activity was examined by DPPH free radical scavenging assay. The results revealed the variation in phytoconstituents among the 70% ethanol and aqueous extracts of all three plant samples. Among the samples, the 70% ethanol extract of P. calophylla exhibited the highest antioxidant activity with an IC50 value of 94.36 μg/mL, while the aqueous extract of F. neriifolia showed the minimum antioxidant activity with an IC50 value of 902.23 μg/mL. This study indicates that these plant samples possess potent natural antioxidants capable of scavenging free radicals that cause cellular damage and contribute to various diseases in our bodies.